Efficacy of adalimumab in moderate to severe hidradenitis suppurativa: Real life data - Aikaterini Kyriakou; Anastasia Trigoni; Nikiforos Galanis; Dimitrios Sotiriadis; Aikaterini Patsatsi (PAGEPress Publications, 2018)
Hidradenitis suppurativa (HS) is a relapsing, inflammatory disease characterized by painful nodules, abscesses, sinuses track formation and scarring. HS has a great impact on patients' quality of life and its treatment may be really challenging. Adalimumab provides a new therapeutic option for HS. Our aim was to assess the therapeutic potential of adalimumab on patients with HS based on the data from the daily clinical practice of an HS Outpatient Clinic. 19 patients with clinically evident moderate to severe HS, under adalimumab treatment for at least 24 week, participated in this observational, retrospective study. The Hidradenitis Suppurativa Physician's Global Assessment scale, Modified Santorius scale and Dermatology Life Quality Index (DLQI) at baseline, week 4, week 12 and week 24 were retrieved from the records. Both Modified Santorius score and DLQI were significantly decreased during the weeks of evaluation (Friedman's test; P < 0.001). The proportion of patients who achieved clinical response was 10.5% (n = 2) at week 4, 42.1% (n = 8) at week 12 and 63.2% (n = 12) at week 24. Treatment with adalimumab was linked with both clinical remission of HS and improvement of patients' quality of life.